MRGPRX2 antagonist GE1111 attenuated DNFB-induced atopic dermatitis in mice by reducing inflammatory cytokines and restoring skin integrity - Wong, Trevor K.; Choi, Ye Gi; Li, Philip H.; Chow, Billy K. C.; Kumar, Mukesh (Frontiers in Immunology, 2024)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder characterised by itching, erythema, and epidermal barrier dysfunction. The pathogenesis of AD is complex and multifactorial; however, mast cell (MC) activation has been reported to be one of the crucial mechanisms in the pathogenesis of AD. The MC receptor Mas-related G protein-coupled receptor-X2 (MRGPRX2) has been identified as a prominent alternative receptor to the IgE receptor in causing MC activation and the subsequent release of inflammatory mediators. The current study aimed to evaluate the therapeutic effect of a novel small molecule MRGPRX2 antagonist GE1111 in AD using in vitro and in vivo approaches. We developed an in vitro cell culture disease model by using LAD-2 MC, HaCaT keratinocytes and RAW 264.7 macrophage cell lines. We challenged keratinocytes and macrophage cells with CST-14 treated MC supernatant in the presence and absence of GE1111 and measured the expression of tight junction protein claudin 1, inflammatory cytokines and macrophage phagocytosis activity through immunohistochemistry, western blotting, RT-qPCR and fluorescence imaging techniques. In addition to this, we developed a DFNB-induced AD model in mice and evaluated the protective effect and underlying mechanism of GE1111. Our in vitro findings demonstrated a potential therapeutic effect of GE1111, which inhibits the expression of TSLP, IL-13, MCP-1, TNF-α, and IL-1ß in MC and keratinocytes. In addition to this, GE1111 was able to preserve the expression of claudin 1 in keratinocytes and the phagocytotic activity of macrophage cells. The in vivo results demonstrated that GE1111 treatment significantly reduced phenotypic changes associated with AD (skin thickening, scaling, erythema and epidermal thickness). Furthermore, immunohistochemical analysis demonstrated that GE1111 treatment preserved the expression of the tight junction protein Involucrin and reduced the expression of the inflammatory mediator periostin in the mouse model of AD. These findings were supported by gene and protein expression analysis, where GE1111 treatment reduced the expression of TSLP, IL-13, and IL-1ß, as well as downstream signalling pathways of MRGPRX2 in AD skin lesions. In conclusion, our findings provide compelling in vitro and in vivo evidence supporting the contribution of MRGPRX2-MC interaction with keratinocytes and macrophages in the pathogenesis of AD.